Bullying and Belonging: Teachers’ Reports of School Aggression - Jones, Sian Emily; Manstead, Antony S.R.; Livingstone, Andrew G (Frontline Learning Research, 2014)
Research on bullying has confirmed that social identity processes and group-based emotions are pertinent to children’s responses to bullying. However, such research has been done largely with child participants, has been quantitative in nature, and has often relied on scenarios to portray bullying. The present paper departs from this methodology by examining group processes in qualitative reports of bullying provided by teachers. Fifty-one teachers completed an internet-based survey about a bullying incident at a school where they worked. Thematic analysis of survey responses concerned two core themes in the reports: (a) children ganging up on another child and (b) children sticking together to protect each other. There was evidence that children act in specific ways, in line with social identity processes, in order to support or resist bullying. There was also evidence that teachers understand bullying to be a group phenomenon. The implications of these findings for anti-bullying interventions are discussed.